Church profiles book II basic information on member churches and associate members of the National Council of Churches in the Philippines. - National Council of Churches in the Philippines (Quezon City National Council of Churches in the Philippines, Library and Documentation Office, 1998)
Handbook which aims to give readers vital information and statistics on the National Council of Churches in the Philippines' members. Through this compact and concise resource material, readers are given a clear picture of the history, policy and programs of the member churches and associate members of the NCCP, the biggest grouping of mainstream protestant and non- Roman Catholic churches in the Philippines. The handbook also features the NCCP profile, a list of churches in key cities in the Philippines, the past officers of the NCCP from 1964- 99, and general information on the past NCCP conventions from 1963-97.
The NCCP is an organization of non-Roman Catholic, Evangelical, and Protestant churches in the Philippines. This booklet is a basic introduction to its members. These include the Apostolic Catholic Church, Christ Centered Church, Convention of Philippine Baptist Churches, Episcopal Church in the Philippines, Iglesia Evangelica Metodista en las Islas Filipinas, Iglesia Filipina Independiente, Iglesia Unida Ecumenical, Lutheran Church in the Philippines, The Salvation Army, United Church of Christ in the Philippines, and United Methodist Church. It includes information on non-church member institutions and organizations. Each article includes the date of establishment, short history, objectives, and contact information as well as black and white illustrations and the church's logo or insignia.
Keywords: Protestant churches -- Philippines -- Directories